2015
DOI: 10.1002/anie.201505985
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection of Photothermal and Photoelectrocatalytic Effects Induced by SPR from Au@Pt Nanoparticles

Abstract: The surface plasmon resonance (SPR) induced photothermal and photoelectrocatalysis effects are crucial for catalytic reactions in many areas. However, it is still difficult to distinguish these two effects quantitatively. Here we used surface-enhanced Raman scattering (SERS) to detect the photothermal and photoelectrocatalytic effects induced by SPR from Au core Pt shell Nanoparticles (Au@Pt NPs), and calculated the quantitative contribution of the ratio of the photothermal and photoelectrocatalysis effects to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 177 publications
(145 citation statements)
references
References 38 publications
4
139
0
2
Order By: Relevance
“…Since 2010, various experimental and theoretical results have supported the production of DMAB from pATP by plasmon-driven surface-catalyzed chemical reactions. [61][62][63][64][65][66][67][68][69][70][71][72] Adv. Optical Mater.…”
Section: Hot Electron-induced Surface-catalyzed Chemical Reactionsmentioning
confidence: 99%
“…Since 2010, various experimental and theoretical results have supported the production of DMAB from pATP by plasmon-driven surface-catalyzed chemical reactions. [61][62][63][64][65][66][67][68][69][70][71][72] Adv. Optical Mater.…”
Section: Hot Electron-induced Surface-catalyzed Chemical Reactionsmentioning
confidence: 99%
“…Regarding the mechanism of the plasmon‐enhanced electrocatalytic activity of the Au@Pd NPCs and NPs, it is noteworthy that there was a lag in the catalytic response to visible light irradiation (Figure b,c), suggesting that the primary mechanism of the enhancement is the plasmonic heating like the previous studies, as hot carrier (electron and hole) driven processes are characterized by almost immediate system response. To further verify the underpinning mechanism of the plasmon‐enhanced electrocatalysis, the surface temperatures of the Au@Pd NPCs and NPs after illumination were estimated according to the reported method, in which the final temperature on the surface of nanostructures after illumination is calculated from the SERS peak position of the NC stretching mode, ν(NC), of 4‐methoxyphenyl isocyanide (4‐MPI) adsorbed on nanostructures, as the ν(NC) of 4‐MPI is sensitive to the temperature. As shown in Figure S17 (Supporting Information), the ν(NC) peak of 4‐MPI adsorbed on the Au@Pd NPCs significantly red‐shifted (13 cm −1 ) after 633 nm laser irradiation (0.6 mW) for 70 min compared to the Au@Pd NPs.…”
Section: Resultsmentioning
confidence: 55%
“…Specifically, core–shell NPs containing Au cores and catalytically active shells showed promoted electrocatalytic performance toward alcohol oxidation under visible light irradiation, which was attributed to synergism between plasmonic and catalytic functions of cores and shells, respectively. From quantitative analyses on the contribution of the plasmonic effects to the electrocatalytic activity, Yang et al found that the enhanced electrocatalytic activity is contributed mostly by the photothermal effect, of which contribution is larger than 80% . Considering the amplified plasmonic function and intact catalytic activity of the Au@M NPCs relative to their NP counterparts, it can be reasoned that the present Au@M NPCs can be a highly promising platform for plasmon‐enhanced electrocatalysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] When the incident light frequency can match the inherent oscillation frequency of free electrons within metal surfaces, it will trigger the generation of photoexcited hot electrons, followed by the oscillation with incident electromagnetic field. [32] Benefiting from the achievements in the area of nanoscience and nanotechnology, there have been numerous kinds of metals used as plasmonic photothermal agents so far, such as gold (Au), [33][34][35] silver (Ag), [36] platinum, [37] palladium, [38] and aluminum. [31] On the basis of above interaction mechanism, Orrit and co-workers first reported a plasmonic photothermal effect of nanometer-sized gold particles in 2002.…”
Section: Plasmonic-based Solar Absorbersmentioning
confidence: 99%